Produção e caracterização preliminar de variantes de L-asparaginase II de Escherichia coli de menor potencial imunogênico: combinação de estudos in silico e in vitro - Caetano, Ludmilla Freire (2020)
L- asparaginase type II (LASNase II) is a therapeutic protein used in the treatment of Acute Lymphoid Leukemia (ALL), promoting the depletion in serum asparagine which is essential in the proliferation of tumor cells. Its main productive source is bacterial, and common available formulations are from Erwinia chrysanthemi and Escherichia coli. Despite their anti-leukemic efficiency, hypersensitivity reactions and pancreatitis in patients are attributed to their antigenicity, since there is the activation and processing of their immunogenic epitopes as antigens to the cells of the immune system, and consequent resistance by the production of Anti-asp antibodies. Bioinformatics tools applied to the prediction of immunogenic fragments and Protein Engineering techniques can be used in deimmunization by deleting specific peptide sequences, which enables the development of biobetters. Based on a work of structural bioinformatics group at Fiocruz Ceará, in which molecular identification methods for the affinity of the E. coli LASNase II antigenic epitopes (ECLASNaseII) and the MHC II (Histocompatibility II Complex Complex) binding gap ) were developed, the objective of this work was to combine such in silico analysis with the site-directed mutagenesis technique in order to generate four variants of ECLASNaseII through cloning, heterologous expression, purification by affinity chromatography, and to promote its biochemical characterization regarding kinetics enzymatic, glutaminase activity, effect of different pH and temperatures and evaluation of the cytotoxic potential of native protein and mutants, as a standard step in determining its immunogenic effect. From the ansB-pETSUMO recombinant vector, mutations were inserted into the gene with the aid of mutagenic primers, and the mutant and native proteins were expressed in bacterial system E. coli Rosetta. After purification by immobilized metal affinity chromatography (IMAC) optimized by the digestion with SUMO protease to remove Histag, the native ECLASNaseII was subjected to biochemical characterization tests by Nesslerization reaction, evaluation of catalysis against different pH (3 to 11) and temperatures (20 to 90 ˚C), enzymatic kinetics (Km and Vmax) and cytotoxic effect by MTT in lymphoid and myeloid tumor lines. The four mutated ECLASNaseII variants did not show any apparent asparaginase activity in the functional assay by the Nessler method. An analysis by simulation of molecular dynamics showed the occurrence of interatomic interactions between the catalytic site residues and the substitute aspartate residue, present in all variants, which may have impaired the interaction with the substrate. This hypothesis seems to be the main cause of the non-functionality of the mutated proteins, which will be proven with the reversal of this mutation and the continuity of the biochemical and functional characterization assays. Keywords: L-asparaginase II, immunogenicity, biobetter.